The effect of nickel-contamination, nitrogen-supply and liming on the chemical composition of perennial ryegrass (Lolium perenne L.) - Sipos, Marianna (Acta Agraria Debreceniensis, 2008)
Plant-production is determined by many production-factors. Each of these factors became subject of research-works through the years, still we state, that studying their interaction is even more important. For studying these interactions we set up a potexperiment, within that the direct effect and the interactions of four factors was inspected: soil, nitrogen-supply, nickel-loading and liming. Experiments were carried out on two soil types with extremely different characters: one was a chernozem soil with good fertility and buffering capacity, the other was a shifting sand soil with low humus-content and buffering capacity. Nitrogensupply and liming was added on two levels, while nickel on three within 12 combinations on each soil types. Plant production was cut two times within the vegetation period. The amount of production and dry matter was weighted, fractured and their element-content was measured by an ICP-detector. Ca-content on the shifting sand soil was determined by all three factors, however the interaction between nickel-loading and liming was also significant. Nitrogen and liming increased Cauptake, that is due to appropriate nutrient-supply and improvement of a better pH-value. On the chernozem soil nitrogen and CaCO3 also increased the Ca-content. This is caused by a better nutrient supply and a higher amount of available Ca-ions. On the shifting sand soil nickel content was increasing parallel to higher nitrogen-dosages. In presence of higher nickelamount the nickel-content of plants was also increasing, still according to liming, this increment was different. On the chernozem soil nitrogen a nickel increased Ni-uptake. However, liming also had a positive effect on Ni-content, that can be explained by the high amount on colloids in the soil, the adsorption of Ni-ions on them and in presence of liming material the replacement of Ca-and Ni-ions. The potassium-content on the shifting sand soil was different in each liming-combination. In combinations without nickel the potassium-content of limed and not limed combinations was on the same level. In not limed combinations by adding nickel potassiumcontent was increasing, while in limed combinations no change was observed. On the chernozem soil by adding liming material the amount of uptaken potassium was decreasing, that is due to the antagonism between Ca- and K-ions.